Job mismatch in early career of graduates under post-communism. Issue 4 (1st July 2014) - Robert, Peter
Abstract : Purpose: – The purpose of this paper is to investigate vertical and horizontal mismatch between education and current occupation for graduates in four post-communist societies: Hungary, Poland, Lithuania and Slovenia. In this way it contributes to the field by exploring how mechanisms, known from previous studies on western societies, affect job mismatch in emerging market economies. Design/methodology/approach: – Two dependent variables are constructed: working in a non-graduate occupation as defined by the ISCO job title depicts vertical mismatch; assessment of the job from the perspective of the fields of study describes horizontal mismatch. Since the dependent variables are dichotomous ones, binary logistic regression models are fitted to the data predicting the incidence of mismatch. Explanatory variables cover mechanisms affecting job mismatch: variation by fields of studies, accumulated work experience during studies, labour market uncertainties during early career, trade off between job safety and job mismatch, persistence of "bad" labour market entry during early career, influence of parental background on school-to-work transition. Findings: – The analysis reveals significant differences for study fields in association with occupational specificity of the disciplines. Only study-related work experience seems to be advantageous to find a matching job. Labour market uncertainties increase the probability of job mismatch. Job safety is more important than a matching job. Originality/value: – Mismatch in first occupation has strong and long-lasting effect on the job match even five years after the graduation. The effect of parental background on job mismatch is curvilinear.